Predictors of Polio Immunization Hesitancy: A Cross-Sectional Study from Mardan Pakistan - Muhammad Ahsan; Hassan Raza; Saba Ali; Muhammad Hassan Raza (ASEAN Journal of Science and Engineering Education, 2021)
We identified groups most at risk of ambiguity and reluctance to take a polio immunization in Mardan, Pakistan general population. A descriptive ad  cross-sectional study was conducted in Mardan to poll 593 Pakistani people on their views regarding polio immunization acceptance. Attitudes and perceptions towards polio immunization acceptance were predicted using logistic regression analysis. Polio immunization acceptance was 55.8%. There was higher vaccination acceptance among females having children of 5 years of age. People residing in rural areas with illiteracy, socioeconomic vulnerability, and not following the proper guidelines by the Government, concerning the safety of vaccine, suffered from food insecurity, and unemployed condition are less likely to accept the polio vaccination than participants who were university graduates, believe in healthcare agencies, residing in urban areas. Adopting polio immunization was also less probable among individuals who thought there was a conspiracy behind them. These measures should include restoring public confidence in national health authorities and organized awareness efforts that provide clear information regarding vaccination safety, effectiveness, and manufacturing.